2020
DOI: 10.1186/s12893-020-0681-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sequential, delayed and simultaneous resection strategies for synchronous colorectal liver metastases

Abstract: Background: The present study aimed to compare the perioperative safety and long-term survival of patients with synchronous colorectal liver metastases undergoing sequential resection (SeR), delayed resection (DeR) and simultaneous resection (SiR). Methods: From January 2007 to December 2016, data from patients undergoing surgery at Peking University Cancer Hospital for synchronous colorectal liver metastases were retrospectively collected. The above three different surgical strategies were compared. Results: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…As such, a recent analysis by Wang et al . [ 20 ] found that the incidence of severe complications was doubled after synchronous resection (26.7%) when compared with the delayed liver resections (11.2%).…”
Section: Discussionmentioning
confidence: 99%
“…As such, a recent analysis by Wang et al . [ 20 ] found that the incidence of severe complications was doubled after synchronous resection (26.7%) when compared with the delayed liver resections (11.2%).…”
Section: Discussionmentioning
confidence: 99%
“…(2) delayed resection (DeR) in which we deliver interval chemotherapy between staged colonic cancer resection and hepatic resection of CRC metastases; and (3) simultaneous resection (SiR), single-stage resection of primary colorectal cancer and liver metastases simultaneously. SiR is performed in patients who fulfil certain criteria (1) the primary tumour was located in the right colon regardless of the tumour disease burden of liver metastases; (2) the tumour disease burden was not heavy, and the tumour number was less than two if the primary tumour was located in the left colon or rectum [38,39].…”
Section: Synchronous Diseasementioning
confidence: 99%
“… 9 , 10 However, the timing of surgery remains controversial. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Some studies suggested that SIH could increase the risk of postoperative complications and perioperative mortality, 11 , 12 , 13 while other studies did not support this conclusion. 14 , 15 , 16 In addition, the difference in long‐term survival is also unclear between the SIH and STH.…”
Section: Introductionmentioning
confidence: 99%
“…However, articles on major hepatectomy in SIH have significantly increased in the past decade. 10 , 11 , 12 , 13 , 14 , 15 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Whether more patients received major hepatectomy can lead to differences in postoperative complications and perioperative mortality between simultaneous major hepatectomy (SIMH) and staged major hepatectomy (STMH) is unclear. And no meta‐analysis has been performed to investigate this issue.…”
Section: Introductionmentioning
confidence: 99%